Development and test–retest reliability of a new, self-report questionnaire assessing healthcare use and personal costs in people with inflammatory bowel disease: the Inflammatory Bowel Disease Resource Use Questionnaire (IBD-RUQ). Issue 1 (25th July 2022) - Roukas, Chris; Syred, Jonathan; Gordeev, Vladimir Sergeevich; Norton, Christine; Hart, Ailsa; Mihaylova, Borislava
Abstract : Background and aims: The increasing prevalence of inflammatory bowel disease (IBD) poses a substantial economic burden globally on health systems and societies. Validated instruments to collect data on healthcare and other service utilisation by patients with IBD are lacking. We developed a self-report patient questionnaire to capture key resource utilisation from health services, patient and societal perspectives. Methods: The IBD Resource Use Questionnaire (IBD-RUQ), developed by a multidisciplinary team, including patients, comprises 102 items across the six categories of outpatient visits, diagnostics, medication, hospitalisations, employment and out-of-pocket expenses over the past three months. The test–retest reliability of the IBD-RUQ was studied by administering it twice among patients with IBD with a 2-week time gap. The intraclass correlation coefficients and the average cost from the healthcare, societal and patient perspectives, between test and retest assessments, overall and by service category, were summarised. Results: The IBD-RUQ captures health service use, employment and out-of-pocket expenses. Of 55 patients who completed the first questionnaire, 48 completed the retest questionnaires and were included in the analyses. Test–retest reliability for categories of medications, diagnostics, specialist outpatient and inpatient services, and days off work due to IBD ranged from moderate to excellent; primary care visits showed more limited reliability. The annualised average self-reported health service, out-of-pocket and loss of productivity costs were £4844, £320 and £545 per patient, respectively. Conclusions: The IBD-RUQ is a reliable and valid self-report measure of resource utilisation in adults with IBD and can be used to measure costs associated with IBD.